A test-bed analysis for seamless MIPv6 handover in heterogeneous environment - Uddin, Mohammad Moshee; Pathan, Al-Sakib Khan; Haseeb, Shariq; Ahmed, Mohiuddin (2011)
Now-a-days, mobile nodes (MNs) are being used with multiple network interfaces so that an MN may have a ubiquitous communication. Mobile Internet Protocol version 6 (MIPv6) allows an MN to maintain the ubiquitous connectivity regardless of any type of network interface while it changes the point of attachment in heterogeneous network environment. In this paper, we have studied a vertical handover with the help of MIPL based test-bed to analyze handoff latency and packet loss. The vertical handover has been considered between Ethernet and Wi-Fi network access. We have analyzed the performance during MN’s handover across the networks. The results show that such type of setting could be used in various practical-oriented consumer applications that need to have mobility feature of nodes.